ByzRev 07.2025.022: Aleksandar Jovanović, Michael Palaiologos and the Publics of the Byzantine Empire in Exile, c.1223–1259: (New Approaches to Byzantine History and Culture). Cham: Palgrave Macmillan 2022. - Ciolfi, Lorenzo Maria (The Byzantine Review, 2025)
Aleksandar Jovanović, Michael Palaiologos and the Publics of the Byzantine Empire in Exile, c.1223–1259 (New Approaches to Byzantine History and Culture). Cham: Palgrave Macmillan 2022. xiii, 255 pp. – ISBN 978-3-031-09277-0